Efficient statistics of the wheel-rail contact stress: cases on track geometric excitation. Issue 9 (2nd September 2021) - Xu, Lei; Zhu, Bin; Abulfathi, Mansur Barhama; Meng, Yichen
Abstract : The wheel-rail contact stress solution is the precondition for many wheel-rail contact problems, such as wheel-rail contact fatigue, plastic deformation and wear, etc. However, vehicle-track interaction generally shows a high degree of randomness due to the uncertainty of excitations, e.g. track irregularities, in the estimation of wheel-rail contact point positions and contact stresses. Moreover, it is known that track irregularities are massive data, possessing evolution characteristics at time and space domain, thus it will consume much time if directly loading all of them into the vehicle-track interaction process. Regarding this, this work tries to introduce the track irregularity probabilistic model to select representative track irregularity sets with much smaller samples. To guarantee the representativeness of track irregularity data, track irregularities of up to five thousand kilometres are measured to ensure the ergodicity of the power spectral density function (PSD) of the track irregularities. Moreover, a fast-accurate contact model is introduced to extract the stress distribution of the wheel-rail contact patch. By effectively combing the vehicle-track dynamics method and random simulation methods, the wheel and rail contact stresses in amplitude and distribution range can be efficiently quantified from a statistical view.